PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENCEGAHAN KASUS BULYING DI MAS DARUL IHSAN - Khafidah, Wahyu; Jalaluddin, Jalaluddin; Hayati, Hayati; ZA, Tabrani; Nurhayati, Nurhayati (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to find the role of the principal in preventing bullying at MAS Darul Ihsan. The purpose of this bullying study is to find out the bullying that occurs at MAS Darul Ihsan. The purpose of the study is to find out the principal's leadership in preventing bullying at MAS Darul Ihsan. This research method uses a qualitative approach by means of observation, interviews and documentation of the object of research study regarding the prevention of bullying at MAS Darul Ihsan. The results of the study showed that the handling carried out by the principal and stakeholders by providing an understanding to children to respect the rights of others, then children are taught to control their emotions in order to avoid (take preventive actions) to prevent bullying. Other prevention is carried out by making regulations regarding punishment when bullying occurs which has been carried out since the beginning of entering as a student at Darul Ihsan Aceh Besar